A Critical review on Salvadora persica: An important medicinal plant of arid zone - Sunil Kumar,; Champa Rani,; Manisha Mangal, (International Journal of Phytomedicine, 2012)
S. persica is a multipurpose tree with immense ethno-ecological importance and is commonly used for varied medicinal purposes. It is one of the identified plants from among the seventeen plants families that are cited in the Holy Quran. The plant is used as a source of food, fodder, lipids, gum and resins. In addition, it is also valued for rearing honey bees. Its roots are regularly used as tooth brush throughout the country. Besides these the plant is also grown to provide shelter-belts and windbreakes for agriculture crops. It is distributed throughout the arid and semi-arid ecosystem of world and helps in reclamation of sand dune habitats and saline soils in arid ecosystems. However, its population suffers from serious environmental problems such as deforestation, soil degradation, loss of biodiversity and unsustainable livelihoods. S. persica has high medicinal, economic and ecological values in arid and semiarid ecosystem. Nevertheless, its conservation status is highly threatened and detailed ecological study of S. persica is suggested to conserve its remaining population.